Sputtered magnetite thin films on polymer substrates for flexible spintronics - Ansari, Mohammad Shahnawaze (2021)
For flexible and wearable spintronics, it has thus far been a challenge to develop a magnetic material/polymer heterostructure at room temperature due to the thermal sensitivity of polymers. In order to avoid atomic interdiffusion at the interface, reduce deterioration of the films, and prevent the properties of the substrate material from thermal treatment, development of such heterostructures is essential to accomplish at room temperature. Therefore, integration of magnetite (Fe3O4) thin films with the polymer substrates to construct a thermally stable flexible spintronic component is of great demand. The primary objective of this research work was to optimize the parameters for room temperature growth of ~100 nm thick Fe3O4 films through reactive sputtering by flowing oxygen (O2) and argon (Ar) in the ratio of either 2:20, 3.5:20, or 5:20 sccm on flexible substrates of polycarbonate (PC), polystyrene (PS), polymethyl methacrylate (PMMA), polyvinyl chloride (PVC), and polyethylene terephthalate (PET) developed by drop casting method with a thickness of ~250 µm and defect free surfaces. The results showed that the films grown on PC, PMMA, and PET exhibited the pure form of Fe3O4 with O2 flow rate of 3.5 sccm. The Verwey transition (Tv) of ~123 K, ~124 K, and ~126 K; saturation magnetization (Ms) of ~220 emu/cm3, ~235 emu/cm3, and ~261 emu/cm3; and magnetoresistance (MR) of -7.1%, -7.3%, and -7.8% under H∥Film plane below 60 KOe at 300 K for 100-nm-thick Fe3O4 film on PC, PMMA, and PET substrates, respectively were observed. It was found that the antiferromagnetically (AFM) coupled antiphase boundaries (APBs) played a crucial role in these features. Hence, in the second stage of this research work, the finest set of electrical and magnetic properties out of the 50, 100, 200, and 400 nm thick Fe3O4 thin films developed on flexible PC with an increase in the deposition time (td) from 165 to 1335 s were examined. The maximum value of Ms ~317 emu/cm3 and MR -8.3% were obtained for 200 nm thick film for Fe3O4/PC heterostructure. However, a Tv of ~125 K confirmed the presence of AFM coupled APBs in this architecture, but a negligible loss was observed under flexibility tests i.e. resistivity, (M-H and MR under H(∥ and‎⊥)Film plane at 300 K) with 90° and 45° of bent angles and cyclability experiments on 100, 200, and 400 bending cycles. Therefore, in the next stage, Fe3O4 films with the same thicknesses were grown at room temperature on flexible PMMA substrates as a function of td. With a detection of Tv of ~127 K which is again a signature effect of APBs, Fe3O4/PMMA heterostructure with a film thickness of 200 nm showed an Ms value of ~354 emu/cm3 and MR of -8.6%, larger than the Fe3O4/PC heterostructure. Furthermore, the Fe3O4/PMMA heterostructure showed <5% deterioration in the value of Ms and MR under flexibility and cyclability tests. In the final stage of this research work, Fe3O4/PET heterostructures with 50 nm to 400 nm of film thickness were developed by the same procedure and the results showed that the Tv for these systems was ~122 K which is an indication of almost APB free growth of Fe3O4 films on PET. Besides that, Ms of ~361 emu/cm3, MR of -8.9%, and a negligible loss under different bending tests in comparison to Fe3O4/(PC or PMMA) heterostructures with the same film thickness proved that Fe3O4/PET heterostructure can be a potential candidate for flexible and wearable spintronics.